Solutions for Vietnam Affordable Housing Database Management - Nguyen, Tuyen; Dung, Tran Khanh; Huong, Nguyen Thu; Huong, Le Lan (International Journal of Sustainable Construction Engineering and Technology, 2022)
Affordable housing database management has become a social concern that requires urgent actions in the context of rapid urbanization, particularly in urban areas. This discussion paper applies literature review, analysis and consolidation as well as modelling approach to identify outstanding issues in affordable housing management in Vietnam nowadays. Based on such findings, the document proposes a solution to collect and develop the sector database to facilitate future management. It suggests data categories, structure, model and procedures to update, manage and exploit Vietnam’s affordable housing management database. The pilot software of the proposed model was formulated based on the application of web-based system technologies such as Web API, OSM (OpenStreetMap), REST (REpresentational State Transfer), SOAP (Simple Object Access Protocol).